A voz do idoso: características clínicas, endoscópicas, vocais e morfológicas - Pessin, Adriana Bueno Benito [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: In the presbyphonia occur several structural changes in the larynx and vocal quality, resulting in vocal symptoms as hoarseness, throat clearing, tremor, low and weak voice, difficulty of singing, etc. Histological studies identify calcification of hyaline cartilage, epithelium and vocal muscle atrophy, decrease of elastic fibers and hyaluronic acid and the increase of collagen fibers in the lamina propria. The videolaryngoscopy exams show vocal folds bowed, prominence of vocal apophysis and atrophy of the vocal folds. In acoustic and auditory perception vocal analysis, we observe hoarseness, breathiness, pneumophonic incoordination, reduced maximum phonation time, increase in vocal acoustic parameters, decreased fundamental frequency in women and increased in men. Objective: To analyze presbyphonia from the clinical, vocal, videolaryngoscopic and morphometric aspects. Methods: Two studies were designed: clinical and morphological. Clinical Study: 72 elderly of both genders, who participated in this study, were divided by age: 60-75 years and 76-90 years. A control group was composed by 40 adults (30-50 years) without vocal symptoms. All participants answered a questioner and were submitted to otoscopy, audiometry, tympanometry, videolaryngoscopy, acoustic and perceptual voice analysis (GRBASI scale). Morphological Study- 30 left vocal folds were removed from 30 cadavers of both genders, 20 elderly (60 to 75 years, n = 10; 76 to 90 years, n = 10) and 10 control patients (30-50 years). Staining Techniques used: H&E; PAS, trichrome Masson (collagen fibers) and Calleja (elastic fibers). Morphometric measurements were performed of the thickness of the epithelium, lamina propria, diameter of the vocal muscle, and the concentration of elastic and collagen fibers (% area) in the superficial and deep layers of lamina propria. The morphometric measurements were performed by the software Image ...

Introdução: Na presbifonia ocorrem diversas modificações estruturais na laringe e na qualidade vocal, resultando em sintomas vocais de rouquidão, pigarro, voz fraca, baixa e trêmula e dificuldade no canto. Estudos histológicos identificam calcificação de cartilagens hialinas, atrofia do epitélio e do músculo vocal, diminuição de fibras elásticas e do ácido hialurônico e aumento das fibras colágenas na lâmina própria Os exames de videolaringoscopias revelam fenda fusiforme, proeminência das apófises vocais e atrofia das pregas vocais. Nas análises vocais perceptivo-auditivas e acústicas constatam-se rouquidão, soprosidade, incoordenação pneumofônica, diminuição do tempo máximo de fonação, aumento nos parâmetros vocais acústicos, diminuição da freqüência fundamental nas mulheres e aumento nos homens. Objetivo: Analisar a presbifonia sob os aspectos clínicos, vocais, videolaringoscópicos e morfométricos. Casuística e Métodos: dois estudos foram desenhados: clínico e morfológico. Estudo Clínico: participaram 72 idosos, de ambos os gêneros, subdivididos por idade: 60-75 anos e 76-90 anos. Foi acrescentado um grupo controle com 40 adultos (30 a 50 anos), sem sintomas vocais. Métodos de avaliação: anamnese, otoscopia, audiometria, timpanometria, videolaringoscopia, análise vocal acústica e perceptivo-auditiva (escala GRBASI). Estudo Morfológico- 30 pregas vocais esquerdas foram removidas de 30 cadáveres de ambos os gêneros, 20 idosos (60 a 75 anos n-10; 76 a 90 anos n-10) e 10 adultos controles (30 a 50 anos). Colorações utilizadas: H&E; PAS, Tricômio de Masson (fibras colágenas) e Calleja (fibras elásticas). Realizadas medidas morfométricas da espessura do epitélio, da lâmina própria, do diâmetro do músculo vocal, da concentração de fibras elásticas e colágenas (% de área) nas camadas superficial e profunda da lâmina própria. As medidas morfométricas foram realizadas pelos...
Keywords: Distúrbios da voz - Cirurgia; Laringe; Idosos; Morfometria